Pengaruh Perubahan Suhu Permukaan Laut (SPL) di Selat Makassar terhadap Curah Hujan di Kota Samarinda dan Makassar pada Fase ENSO - Asyikin, Nurul; Yusuf, Mustaid; Sihotang, Zetsaona; Wiyani, Riski Indah (Jurnal Laut Khatulistiwa, 2026)
Sea Surface Temperature (SST) is a key oceanographic parameter that influences atmospheric processes, particularly weather and climate variability, including rainfall, and its variability is closely linked to large-scale climate phenomena such as ENSO. This study examines the relationship between SST variability in the Makassar Strait and rainfall in Samarinda City and Makassar City under three climate conditions representing ENSO phases: El Niño (2015), normal conditions (2017), and La Niña (2022). Daily SST and rainfall data were converted into monthly mean values and analyzed using Pearson correlation to assess the strength and direction of their relationship. The results show that SST–rainfall correlations in Samarinda City were −0.423 during El Niño conditions, −0.219 during normal conditions, and −0.39 during La Niña conditions, indicating a moderate influence during El Niño and weaker relationships in other phases. In Makassar City, correlation values were −0.331 in 2015, −0.10 in 2017, and +0.69 in 2022, suggesting weak relationships during El Niño and normal conditions but a strong positive relationship during La Niña conditions. Overall, these findings demonstrate that the influence of SST variability in the Makassar Strait on rainfall differs by region and ENSO phase, providing useful insight for developing region-specific rainfall prediction models based on oceanic and climatic variability.